(untitled) (Altre Modernità, 2020)
The protagonist of Lisa Genova’s novel Still Alice, Alice Howland, is a Harvard Professor of Cognitive Psychology who is diagnosed with early-onset Alzheimer’s disease at the age of 50. In order to save traces of her past as it progressively wears away, and to maintain control of her life despite the illness, Alice comes up with several coping strategies. She also creates a support group composed of others suffering from the disease, while submitting to an experimental therapy. The diagnosis of Alzheimer’s disease still leaves no hope for a positive outcome— that is why, according to Martina Zimmermann, a novel about it does not match the survivor narrative type. In any case, as this contribution hopes to convey, a novel such as Still Alice, the author of which is a neuroscientist, can help patients and their families understand what they are dealing with and what to expect, in a narrative that is not intended as a “cure” or a success story, but mostly as an aid to manage the inevitable disappearance of memory, orientation and family relations.